Preparation of solid heterogeneous catalysts for biodiesel production from palm-based feedstock - Theam, Kok Leong (2015)
Palm fatty acid distillate (PFAD) and palm stearin (PS) are side products from physical refining of crude palm oil, and it can be a good alternative feedstock for biodiesel production. In this study, PS and PFAD were chemically converted into biodiesel using solid base and acid catalysts. The reaction parameters of the catalytic reaction were thoroughly investigated and optimized via Response Surface Methodology. The optimal values of these factors were found to be related to the chemical and physical properties of the feedstock. Four catalysts were synthesized and used to produce biodiesel and these were (i) nanoscale calcium methoxide (eMS), (ii) zirconia supported calcium methoxide (eMSS), (iii) sulfated zirconia (SZ) and, (iv) ball-milled sucrose-derived carbon acid catalyst (S400M). eMS catalyst possesses a novel morphology due to the sonication treatment during preparation of the catalyst. The nanoscale particles gave a high surface area which may provide more active sites for reactants to anchor and react. The results showed that eMS has excellent basicity and high catalytic ability as a heterogeneous solid base catalyst. This catalyst gave 94.7 % of biodiesel yield within 3 hours at temperature of 70'C, methanol molar ratio and catalyst loading of 6 and 1 wt% of PS, respectively. Besides, eMSS catalyst gave the highest biodiesel yield of 98 % at temperature of70'C, reaction time of 125 min, using 3 % catalyst loading and methanol to PS molar ratio of 11:1. Furthermore, the recycling experiment results showed it had a longer catalyst lifespan, and the zirconia support had proven to be the good stabilizing agent to the calcium methoxide catalyst. This catalyst appeared to be a promising candidate to replace the existing homogeneous catalysts for biodiesel production as it requires short reaction time with high reusability. Moreover, SZ has been extensively studied and optimized as catalyst for the esterification of free fatty acid in PFAD with methanol. The effect of sonication on the phase structure and its catalytic activity was investigated. TPD-NH3 coupled with mass spectrometer analysis revealed that the first thermal desorption peak of SZ represented the actual acidity of the catalyst. SZ catalyst exhibited a good catalytic performance as a heterogeneous solid acid catalyst which used to esterify PFAD and 97 % of free fatty acid (FFA) conversion was achieved with 2 hours of reaction time, despite its low surface area. A noticeable deactivation of catalyst has been experimentally detected under the optimized reaction conditions. The characterization results showed that the deactivation is due to the leaching of sulfate groups from the catalyst. Furthermore, the other heterogeneous solid acid catalyst i.e. S400M was prepared in the present study which aims to improve the esterification process and reduce the generation of waste from biodiesel production. The experimental results showed that S400M exhibited good catalytic activity in the esterification of PFAD, providing maximum FFA conversion of 94% at optimum parameters. The good catalytic activity of the aforementioned catalyst in the biodiesel reaction could be attributed to the presence of optimal number of catalytically active acid site density on its surface. The mechanochemical treatment was the good tool to improve the catalytic activity of carbon catalyst by adding extra active sites for esterification of FFA and to intensify the acid strength of the catalyst.